2018
DOI: 10.1002/npr2.12042
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic‐pituitary‐adrenal axis differentially responses to morning and evening psychological stress in healthy subjects

Abstract: Aim The hypothalamic‐pituitary‐adrenal (HPA) axis responds to changing environmental demands including psychological stressors. The aim of the present study was to assess whether the time of day effects on the acute response of HPA axis activity to acute psychological stress. Method We studied 27 healthy young subjects. The subjects were participated two experiments as follows. In the first experiment, subjects were instructed to keep their regular sleep schedule for 2 weeks which were measured by using a wris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
0
15
0
4
Order By: Relevance
“…Furthermore, diurnal cortisol profile, cortisol awaking response and total cortisol excretion over the day are associated with each individual's chronotype classifying, one as rather a morning or evening type [32][33][34]. Additionally, recent studies observed that the hypothalamic-pituitary-adrenal (HPA) response to acute psychological and to high-intensity exercise stress is more pronounced in the morning than in the evening, correlating with the circadian rhythm of cortisol synthesis [35,36]. This finding is in line with our observations of a maintained circadian cortisol rhythm despite higher morning concentrations in women.…”
Section: Differential Neurohumoral Response Pattern and Psychologicalmentioning
confidence: 99%
“…Furthermore, diurnal cortisol profile, cortisol awaking response and total cortisol excretion over the day are associated with each individual's chronotype classifying, one as rather a morning or evening type [32][33][34]. Additionally, recent studies observed that the hypothalamic-pituitary-adrenal (HPA) response to acute psychological and to high-intensity exercise stress is more pronounced in the morning than in the evening, correlating with the circadian rhythm of cortisol synthesis [35,36]. This finding is in line with our observations of a maintained circadian cortisol rhythm despite higher morning concentrations in women.…”
Section: Differential Neurohumoral Response Pattern and Psychologicalmentioning
confidence: 99%
“…It is well known that cortisol levels are highest on awakening and decrease throughout the day. [51][52][53] For example, Laudat et al 50 showed an average cortisol level of 0.56 versus 0.14 µg/dL between 8:00 A.M. and 8:00 P.M. in healthy adults. To our knowledge, only one study in a similar cohort of parents observed comparable cortisol findings to those in our current study.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that, under physiological conditions, cortisol is released according to a circadian rhythm characterized by the lowest level at the night, the maximum level in the early morning in response to events such as waking up, and a progressive decrease reaching the minimum value by the end of the day [49,50].…”
Section: Discussionmentioning
confidence: 99%
“…The factors involved in these responses may be different. In addition to sleep deprivation, it is believed that the particular psychophysical commitment required by the activity conducted on the road plays a fundamental role [49][50][51][52][53][54]. Previous research indicated that exposure to shift work during one's occupational career causes disruption of the circadian time.…”
Section: Discussionmentioning
confidence: 99%